Pengaruh Pemahaman Pajak dan Sosialisasi Pajak terhadap Kepatuhan Wajib Pajak dalam Membayar Pajak Bumi dan Bangunan di Desa Penfui Timur Kecamatan Kupang Tengah Kabupaten Kupang Provinsi NTT - Dian Honi Millenium Mamun; David R. E. Selan; Ariyon S. Ndun (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to analyze the effect of Tax Understanding and Tax Socialization on Taxpayer Compliance in Paying Land and Building Tax (PBB) for the period 2023–2025. The independent variables used in this study are tax understanding (X1) and tax socialization (X2), while the dependent variable is taxpayer compliance in paying PBB (Y). The research method employed is a quantitative method with a descriptive approach. The population in this study consisted of PBB taxpayers in East Penfui Village, with a sample size of 50 respondents determined using purposive sampling technique. Data collection was carried out through distributing questionnaires to respondents. Data analysis used the Statistical Product and Service Solutions (SPSS) application, which included validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, t-test, F-test, and the coefficient of determination (R²). The results of the study indicate that tax understanding has a positive and significant effect on taxpayer compliance in paying PBB. Tax socialization also has a positive and significant effect on taxpayer compliance. Simultaneously, tax understanding and tax socialization have a significant effect on taxpayer compliance in paying PBB. The coefficient of determination value indicates that the variables of tax understanding and tax socialization are able to explain the variation in taxpayer compliance, while the remainder is influenced by other variables outside the study. Based on these findings, it is expected that the village government and related agencies can enhance tax socialization activities and provide education to the community so that taxpayers' understanding improves, thereby increasing compliance in paying PBB.